What is sectheta+cos^2theta -costheta in terms of sintheta?

1 Answer
Jan 22, 2016

=sin^2(theta)/sqrt(1-sin^2(theta)) + 1- sin^2(theta)

Explanation:

sec(theta) + cos^2(theta) - cos(theta)

To simplify in terms of sin(theta) let us write sec(theta) as 1/cos(theta)

=1/cos(theta) + cos^2(theta) - cos(theta)

=1/cos(theta) + (cos^2(theta)cos(theta))/cos(theta) - (cos(theta)cos(theta))/cos(theta)

= (1+cos^3(theta)-cos^2(theta))/cos(theta)

=(1-cos^2(theta) + cos(theta)cos^2(theta))/cos(theta)

=(sin^2(theta)+sqrt(1-sin^2(theta))(1-sin^2(theta)))/sqrt(1-sin^2(theta)

If you need it can be simplified further as

=sin^2(theta)/sqrt(1-sin^2(theta)) + (sqrt(1-sin^2(theta))(1-sin^2(theta)))/sqrt(1-sin^2(theta)

=sin^2(theta)/sqrt(1-sin^2(theta)) + (cancel(sqrt(1-sin^2(theta)))(1-sin^2(theta)))/cancel(sqrt(1-sin^2(theta))

=sin^2(theta)/sqrt(1-sin^2(theta)) + 1- sin^2(theta)